1999
DOI: 10.1046/j.0909-8836.1999.eos107612.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of self‐reported hand eczema and skin symptoms associated with dental materials among Swedish dentists

Abstract: In the present study we investigated the prevalence of self-reported hand eczema as well as subjective associations between skin symptoms and composite/bonding or other dental materials among Swedish dentists. A questionnaire on skin symptoms, atopy, occupational experience, and other background factors was sent to a random sample (n=3,500) of all dentists licensed since 1965. This group corresponds to about half of the country's occupationally active dentists. The response rate was 88%. The questionnaire had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 18 publications
0
55
0
1
Order By: Relevance
“…A questionnaire on skin and airway symptoms, atopy, occupational experience, and other background factors was sent by mail to the 3500 dentists in 1996 (8). It included questions on whether the dentist had contacted a physician owing to work-related skin or airway symptoms, about sick leave caused by these symptoms, or about notification of occupational disease and whether the symptoms had caused changes of occupation or work tasks.…”
Section: Questionnairementioning
confidence: 99%
See 2 more Smart Citations
“…A questionnaire on skin and airway symptoms, atopy, occupational experience, and other background factors was sent by mail to the 3500 dentists in 1996 (8). It included questions on whether the dentist had contacted a physician owing to work-related skin or airway symptoms, about sick leave caused by these symptoms, or about notification of occupational disease and whether the symptoms had caused changes of occupation or work tasks.…”
Section: Questionnairementioning
confidence: 99%
“…The hands are exposed to skin irritants and to contactsensitizing substances used in dental materials. Several reports of skin reactions to dental materials, especially acrylates, among dental personnel were published in the 1990s (1)(2)(3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies have shown that many of these compounds are leaching from the filling materials even after adequate polymerization [1][2][3][4][5][6][7]. It is known that some of the ingredients in the resin-based materials have cytotoxic [8][9][10][11][12][13][14], genotoxic [12,13] or allergenic effects [15][16][17][18] and/or exhibit estrogenic activity in vitro [19,20]. By use of chromatographic and mass spectrometric techniques, monomers and additives have been identified in aqueous and alcohol extracts of polymerized dental fillings [1][2][3][4][5][6]21].…”
Section: Introductionmentioning
confidence: 98%
“…Few studies showed that the 1-year median prevalence of hand eczema in the general population was 9.7% (11.4% among women and 5.4% among men) and that the 1-year weighted average prevalence was 9.1% (10.5% among women and 6.4% among men) (Lantinga et al, 1984;Agrup, 1969;Peltonen, 1979;Menné et al, 1982;Kavli & Forde, 1984;Meding & Swanbeck, 1987;Meding & Jarvholm, 2002;Ortengren, 1999;Meding et al, 2001;Brisman J et al, 1998;Montnemery et al, 2005;Bo et al, 2008;Fowler et al, 2006;Hald et al, 2008;Svedman et al, 2007;Lind et al, 2007).…”
Section: Prevalence Of Hand Eczemamentioning
confidence: 99%